Perceptions and reasons for legume consumption in Mexico. Issue 6 (11th November 2019) - Monge, Adriana; Macias, Lorena; Campos, Hannia; Lajous, Martin; Mattei, Josiemer
Abstract : Purpose: Legume consumption has decreased in Mexico as part of a global nutrition transition that has shifted the intake of healthy traditional foods to more processed unhealthy foods. This study aims to assess preferences and patterns of legumes consumption, attitudes toward legumes and reasons to consume legumes among adults in Mexico City. Design/methodology/approach: A convenience sample of 86 adult participants living in the Mexico City region completed interviewer–administered surveys. Findings: The participants had an average age of 42.9 years (SD 13.5) and 51.2 per cent were women. Most reported consuming legumes = 1/week (59.5 per cent) and =1/3 cup/meal (52.4 per cent) and using corn tortillas to accompany legumes (83.3 per cent). Participants reported consuming 7 out of 15 types of legumes probed, of which black beans (96 per cent), lentils (79 per cent) and garbanzo beans (64 per cent) were more frequently consumed. Participants had positive (vs negative) perceptions about legumes' taste (96 per cent), nutritional value (88 per cent), tradition (80 per cent), cost (75 per cent), availability (75 per cent) and health effect (73 per cent), but not for their digestive effect (37 per cent). The main reasons for participants to currently consume legumes were their taste (93 per cent), nutritional value (49 per cent) and affordable cost (48 per cent); whereas main reasons for potentially consuming more legumes were their nutritional value (63 per cent) and health effect (64 per cent). Practical implications: Legume intake in Mexico is lower than the recommended 1.5-2 servings per day (1 serving = 1/2 cup), despite favorable perceptions and reasons to consume them. The identified characteristics, attitudes and reasons for consuming legumes could inform interventions to increase intake of this traditional food in Mexico. Originality/value: Studies on attitude and reasons for food consumption are seldom conducted, yet they are valuable in shaping tailored strategies for eating behavior change.